Making soy sauce from defatted soybean meal without the mejus process by submerged cultivation using thermophilic bacteria - Hur, Jeong Min (J Food Sci Technol, 2014)
The diversity of thermophilic bacteria was not significantly altered while growing in a defatted soybean meal (DFSM) slurry at 60 °C for 10, 20, and 30 days. Five species of thermophilic bacteria, which belong to the genera Aeribacillus (temperature gradient gel electrophoresis [TGGE] band no. 1), Saccharococcus (TGGE band no. 2), Geobacillus (TGGE band no. 3), Bacillus (TGGE band no. 4), and Anoxybacillus (TGGE band no. 5), were detected in the fermenting DFSM slurry. The cell-free culture fluid obtained from the fermenting DFSM slurry on day 14 hydrolyzed starch and soy protein at 60 °C but not at 30 °C. Soy sauce (test soy sauce) was prepared from the fermented DFSM slurry after a 30 day cultivation at 60 °C and a 60 day ripening at 45 °C. Free amino acid (AA) and organic acid contents in the soy sauce increased in proportion to the fermentation period, whereas ammonium decreased proportionally. Mg and Ca contained in the soy sauce decreased proportionally during fermentation and were lower than those in the non-fermented DFSM extract (control). Spectral absorbance of soy sauce prepared from the fermented DFSM slurry was maximal at 430 nm and increased slightly in proportion to the fermentation period. The aroma and flavor of the test soy sauce were significantly different from those of traditional Korean soy sauce. Conclusively, soy sauce may be prepared directly from the fermented DFSM slurry without meju-preparing process and fermentation period may be a factor for control of soy sauce quality.